MiR-665 Regulates Vascular Smooth Muscle Cell Senescence by Interacting With LncRNA GAS5/SDC1 - Chen, Tianbin; Liang, Qingyang; Xu, Jialin; Zhang, Yanan; Zhang, Yi; Mo, Liping; Zhang, Li (Frontiers in Cell and Developmental Biology, 2021)
Background: Vascular aging is considered a special risk factor for cardiovascular diseases, and vascular smooth muscle cells (VSMCs) play a major role in aging-related vascular remodeling and in the pathological process of atherosclerosis. Recent research has reported that long non-coding RNA/microRNA (lncRNA/miRNA) is a critical regulator of cellular senescence. However, the role and mechanism of lncRNA GAS5/miR-665 axis in VSMC senescence remain incompletely understood. Methods: Cellular senescence was evaluated using senescence-associated β-gal activity, the NAD+/NADH ratio, and by immunofluorescence staining of γH2AX immunofluorescence. Differentially expressed miRNAs (DEMs) were identified by miRNA microarray assays and subsequently validated by quantitative real-time PCR (qRT-PCR). A dual luciferase reporter assay was conducted to confirm the binding of lncRNA GAS5 and miR-665 as well as miR-665 and syndecan 1 (SDC1). Serum levels of miR-665, lncRNA GAS5, and SDC1 in 93 subjects were detected by qRT-PCR. The participants were subdivided into control, aging, and early vascular aging (EVA) groups, and their brachial-ankle pulse wave velocity (baPWV) was measured. Results: A total of 20 overlapping DEMs were identified in young and old VSMCs via microarray analysis. MiR-665 showed a significant alteration and, therefore, was selected for further analysis. Upregulation of miR-665 was found in aging VSMCs, and downregulation of miR-665 caused an inhibition of VSMCs senescence. Subsequently, the dual luciferase reporter assay determined the binding site of miR-665 with the 3′-UTR of lncRNA GAS5 and SDC1. Increased expression of lncRNA GAS5 expression inhibited the miR-665 level and VSMC senescence. However, as shown in rescue experiment results, either miR-665 overexpression or SDC1 knockdown significantly reversed the effects of lncRNA GAS5 on VSMC senescence. Finally, compared with that of the control group, miR-665 was highly expressed in serum samples in the aging and EVA groups, especially in the EVA groups. On the contrary, serum levels of lncRNA GAS5 and SDC1 were lower in these two groups. Collectively, in the aging and EVA groups, miR-665 expression was negatively correlated with lncRNA GAS5 and SDC1 expression. Conclusion: miR-665 inhibition functions as a vital modulator of VSMC senescence by negatively regulating SDC1, which is achieved by lncRNA GAS5 that sponges miR-665. Our findings may provide a new treatment strategy for aging-related cardiovascular diseases.